Preclinical Model of Stereotactic Ablative Lung Irradiation Using Arc Delivery in the Mouse: Is Fractionation Worthwhile? - Bertho, Annaïg; Dos Santos, Morgane; Braga-Cohen, Sarah; Buard, Valérie; Paget, Vincent; Guipaud, Olivier; Tarlet, Georges; Milliat, Fabien; François, Agnès (Frontiers in Medicine, 2021)
Lung stereotactic body radiation therapy is characterized by a reduction in target volumes and the use of severely hypofractionated schedules. Preclinical modeling became possible thanks to rodent-dedicated irradiation devices allowing accurate beam collimation and focal lung exposure. Given that a great majority of publications use single dose exposures, the question we asked in this study was as follows: in incremented preclinical models, is it worth using fractionated protocols or should we continue focusing solely on volume limitation? The left lungs of C57BL/6JRj mice were exposed to ionizing radiation using arc therapy and 3 x 3 mm beam collimation. Three-fraction schedules delivered over a period of 1 week were used with 20, 28, 40 and 50 Gy doses per fraction. Lung tissue opacification, global histological damage and the numbers of type II pneumocytes and club cells were assessed 6 months post-exposure, together with the gene expression of several lung cells and inflammation markers. Only the administration of 3 x 40 Gy or 3 x 50 Gy generated focal lung fibrosis after 6 months, with tissue opacification visible by cone beam computed tomography, tissue scarring and consolidation, decreased club cell numbers and a reactive increase in the number of type II pneumocytes. A fractionation schedule using an arc-therapy-delivered 3 fractions/1 week regimen with 3 x 3 mm beam requires 40 Gy per fraction for lung fibrosis to develop within 6 months, a reasonable time lapse given the mouse lifespan. A comparison with previously published laboratory data suggests that, in this focal lung irradiation configuration, administering a Biological Effective Dose ≥ 1000 Gy should be recommended to obtain lung fibrosis within 6 months. The need for such a high dose per fraction challenges the appropriateness of using preclinical highly focused fractionation schedules in mice.